Pengaruh Profitabilitas, Likuiditas, dan Struktur Aset terhadap Struktur Modal - Alvin Aisyah Rahmah; Anwar Hariyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify the influence of profitability, liquidity, and asset structure on the capital structure of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The study spanned five years, from 2019 to 2023. Of the total 15 companies in the population, 7 companies were selected as samples using a purposive sampling method. The research data were sourced from annual financial reports accessed through the official IDX website. Data processing was carried out using multiple linear regression methods. Capital structure was measured using two indicators: the Debt to Equity Ratio (DER) and the Debt to Asset Ratio (DAR). The analysis results showed that profitability had no effect on these two capital structure indicators. Conversely, liquidity and asset structure were shown to influence both DER and DAR. This study provides insight into the factors influencing debt financing decisions in pharmaceutical companies and their implications for the company's financial stability.